PENGHITUNGAN OTOMATIS JUMLAH SEL DARAH MERAH DAN IDENTIFIKASI FASE PLASMODIUM FALCIPARUM MENGGUNAKAN OPERASI MORFOLOGI - Adi Pamungkas; Kusworo Adi; Choirul Anam (Youngster Physics Journal, 2012)
Malaria disease still a public health issue in Indonesia. The incidence of malaria in Indonesia is increasing every year. The cause of malaria is a parasite of the genus plasmodium that infected red blood cells through the bite of Anopheles mosquitoes. One of plasmodium type that often the cause of malaria in Indonesia is the plasmodium falciparum. This type of plasmodium causes malignant tertian malaria which threatening for the sufferer’s life. This study’s function is to design a program that capable automatically to calculate the total number of red blood cells, the number of parasites, and identified the plasmodium falciparum phase. The image processing of red blood cells in digital using morphological operations. The results of the testing program has been designed showed the correlation coefficient for counting the total number of red blood cells is 0.997, the validation value for parasit counting is 87.5%, and validation value for phase identification of plasmodium falciparum is 87.5%. Key words : red blood cell, falciparum, calculation, identification, automatic http://ejournal-s1.undip.ac.id/index.php/bfd/article/view/63